Perspective of Key Healthcare Professionals on Antimicrobial Resistance and Stewardship Programs: A Multicenter Cross-Sectional Study From Pakistan - Hayat, Khezar; Rosenthal, Meagen; Gillani, Ali Hassan; Chang, Jie; Ji, Wenjing; Yang, Caijun; Jiang, Minghuan; Zhao, Mingyue; Fang, Yu (Frontiers in Pharmacology, 2020)
Background: Antimicrobial resistance (AMR) is an increasing global threat, and hospital-based antimicrobial stewardship programs (ASPs) are one of the effective approaches to tackle AMR globally. This study was intended to determine the attitude of key healthcare professionals (HCPs), including physicians, nurses, and hospital pharmacists towards AMR and hospital ASPs. Methods: A cross-sectional study design was used to collect data from HCPs employed in public teaching hospitals of Punjab, Pakistan, from January 2019 to March 2019. A cluster-stratified sampling method was applied. Descriptive statistics, Mann Whitney and Kruskal Wallis tests were used for analysis. Results: A response rate of 81.3% (881/1083) for the surveys was obtained. The majority of the physicians (n=247, 60.2%) perceived AMR to be a serious problem in Pakistani hospitals (p<0.001). Most of the HCPs considered improving antimicrobial prescribing (n=580, 65.8%; p<0.001) accompanied by the introduction of prospective audit with feedback (n=301, 75.8%; p<0.001), formulary restriction (n=227, 57.2%; p=0.004) and regular educational activities (n=300, 75.6%; p=0.015) as effective ASP methods to implement hospital ASPs in Pakistan. A significant association was found between median AMR and ASP scores with age, years of experience, and types of HCPs (p<0.05). Conclusions: The attitude of most of the HCPs was observed to be positive towards hospital-based ASPs regardless of their poor awareness about ASPs. The important strategies, including prospective audit with feedback and regular educational sessions proposed by HCPs, will support the initiation and development of local ASPs for Pakistani hospitals.